2015
DOI: 10.1002/adhm.201400685
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Excited Luminescence Chemical Imaging of Bacterial Growth on Surfaces Implanted in Tissue

Abstract: We develop a pH sensor film that can be coated on an implant surface and imaged using a combination of X-ray excitation and visible spectroscopy to monitor bacterial infection and treatment of implanted medical devices (IMDs) through tissue. X-ray scintillators in the pH sensor film generate light when an X-ray beam irradiates them. This light first passes through a layer containing pH indicator that alters the spectrum according to pH, then passes through tissue where it is detected by a spectrometer. A refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…Similar to other scintillator-based imaging techniques, [18] radioluminescence microscopy uses scintillator properties to study biological processes on a physical scale not previously possible. Our results indicate that the spatial resolution of radioluminescence spectroscopy is dramatically impacted by the properties of the scintillator used.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other scintillator-based imaging techniques, [18] radioluminescence microscopy uses scintillator properties to study biological processes on a physical scale not previously possible. Our results indicate that the spatial resolution of radioluminescence spectroscopy is dramatically impacted by the properties of the scintillator used.…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of the system is limited to the size of the x-ray beam that excites the particles as well as the thickness of the scintillator and pH sensor films, and the thickness of any opaque well targets. In previous studies, we showed that submillimeter knife-edge resolution is acquired with submillimeter X-ray beams 15, 16 , and that the resolution can be reduced by using a larger collimated beam 13 . Here an IFG iMOXS/1-MFR X-ray source (Fischer Technology Inc, Windsor, CT) was used with a slightly focusing polycapillary X-ray optic and a 51 mm working distance.…”
Section: Xelci Of Implanted Medical Device Surface Phmentioning
confidence: 99%
“…In this case, the scintillator is Gd2O2S:Eu, which emits light at 620 nm and 700 nm, and the light modulator is bromocresol green, a pH-sensitive film, which absorbs more 620 nm light at high pH, than at low pH; the 700 nm peak is minimally absorbed regardless of pH, and serves as a spectral reference signal. 13 Above the pH sensitive film is tissue which ranges in thickness depending on the site of implantation. In order to image these sensors, sample (or an x-ray and collection optics) are mounted to an x-y linear stage which causes the x-ray spot to scan across the sensor while pH measurements are acquired at each point.…”
Section: Xelci Of Implanted Medical Device Surface Phmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 The environment adjacent to an infected implant surface is reportedly in the range of pH 4 -6 depending on location and other factors. [27][28][29] These acidic regions play a critical role in biofilm resistance to antimicrobials because low pH affects antibiotic chemistry, host innate immune response, and bacterial metabolism. 30 According to the literature, low pH can be expected during the normal inflammatory phase of necrosis and hematoma formation post-surgery, with sustained acidosis seen with infection or severe chronic inflammation and a return to physiological pH with normal healing.…”
mentioning
confidence: 99%